Finite element analysis to clarify effect of joint congruity on stress at articular surface of thumb carpometacarpal joint - MURAI, Atsuro; TADA, Kaoru; TACHIYA, Hiroshi; TAMAI, Atsuya; KUROSAWA, Akihiro; HIGUCHI, Masahiro (Journal of Biomechanical Science and Engineering, 2025)
Osteoarthritis (OA) of the thumb carpometacarpal (CMC) joint is a common disease in hand OA. Low joint congruity could increase articular stress in the CMC joint and is thus considered among the risk factors for CMC OA. However, this relationship has not been clarified. This study aimed to examine whether low joint congruity correlated with high stress on the articular surface of the CMC joint. CT images were obtained for 14 healthy subjects in eight static limb positions during flexion and extension, and 3D CMC joint models were created. First, cross-sectional images of the CMC joint in the dorsal–volar and radial–ulnar directions were acquired, and the curvature radius ratio between the trapezium and the first metacarpal was then calculated as the joint congruity from these images using image processing and curve fitting. Subsequently, a finite element (FE) model was created, and the maximum value of compressive stress was evaluated. Finally, the correlation coefficients between joint congruity and compressive stress were assessed. As a result, a negative correlation was found between the joint congruity in the volar–dorsal direction and the compressive stress in the trapezium (R = -0.648, p<0.001), showing that low congruity increases the compressive stress on the articular surface of the trapezium. This finding suggests that a low joint congruity contributes to the onset of CMC OA. This could help predict the risk of OA and improve treatments and prevention measures for CMC OA.